Mengukur Kualitas Layanan Perpustakaan di Universitas Potensi Utama Menggunakan Metode Libqual+Tm - Arsela, Feny; Nurhayani, Nurhayani; Yasmin, Nabila (VISA: Journal of Vision and Ideas, 2024)
Library services are the main gateway for library progress, every service provider is obliged to strive to provide the best quality services to the users who come to the library. Therefore, providing library services that are more efficient in terms of time and energy is the main determining factor in service quality from the user's point of view. The aim of this research is to find out what the quality of service is based on a review of measurements using the LibQual+TM method in the library. This research method uses a descriptive quantitative approach. The population in this study are students who are still actively visiting the Main Potential University library. Data collection techniques are observation, documentation, and questionnaires. The conclusion of this research is that the analysis of the quality of the Main Potential library services shows mixed results in several dimensions. In the Affect of Service dimension, users feel quite satisfied with the trustworthiness, polite behavior and reliability of librarians. However, there is dissatisfaction regarding officers' understanding of user needs and responses to questions or concerns. Furthermore, in the Information Control dimension, users assess access to information as inadequate with a low score on the Gap Analysis (AG). Although, they are quite satisfied in searching for information through journals and book collections, there is dissatisfaction regarding access to online information which is also reflected in the Superiority Gap (SG) Analysis. In the Library as Place dimension, users feel quite satisfied with the library facilities and comfortable place. Even though the strategic location and group study area in the library got a low score on the Gap Analysis, users still felt quite satisfied. However, the Superiority Gap Analysis shows dissatisfaction regarding library infrastructure services. Overall, the Adequacy Gap (AG) analysis shows a positive score of 0.48, meaning that the quality of services provided has exceeded the minimum expectations of Main Potential library users/visitors. So, visitors are "quite satisfied" with the quality of existing Main Potential library services. Superiority Gap (SG) analysis shows a negative score of -2.44, meaning that the service quality is rated as "Good", within the tolerance limits, where the service quality is between the minimum acceptable level.